ANALISIS PENERAPAN AKUNTANSI MANAJEMEN LINGKUNGAN PADA HOTEL KINI PONTIANAK - Marsella, Oksi (Jurusan Akuntansi FEB UNTAN, 2025)
This research aims to determine the compliance of Minister of State for the Environment Regulation Number 5 of 2011 regarding Company Performance Rating in Environmental Management with the implementation of environmental management accounting at Hotel Kini Pontianak, and to identify the factors in the implementation of environmental management accounting at Hotel Kini Pontianak. The research method used is a qualitative approach with in-depth interviews with representatives of the management of Hotel Kini Pontianak. The collected data is analyzed and compared with the provisions of Minister of State for the Environment Regulation Number 5 of 2011 regarding Company Performance Rating in Environmental Management in order to perform data reduction. The results of this research indicate that the implementation of environmental management accounting at Hotel Kini Pontianak is not in accordance with Minister of State for the Environment Regulation Number 5 of 2011 regarding Company Performance Rating in Environmental Management.